THE BASIC FACTORS OF DEVELOPING BILINGUALISM IN UZBEKISTAN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article is devoted to discuss the problems of bilingualism and its development in Uzbekistan, analyze the factors of emerging this notion and its stages related to some assumptions. As bilingualism is widely spread in most corners of the world, it has its own historical and other current factors of development in every country. In this article, the main factors of appearance of bilingualism in the condition of Uzbekistan are observed and explored through several needs analysis.